Ambulatory Assessment in the Research on Aging: Contemporary and Future Applications - Brose, Annette; Ebner-Priemer, Ulrich W. (Gerontology (Basel), 2015)
Older adults have surprisingly high levels of well-being, which has been referred to as a paradox in the past. Improved emotion regulation has been suggested to underlie these high levels of well-being. Later life is also a period with enhanced exposure to critical life events, and this comes with risks. During such times, and towards the end of life, emotional well-being may and eventually does decline. We suggest that ambulatory assessment (AA) is ideally suited for the investigation of the above phenomena and for intervention purposes. More precisely, AA can be used to thoroughly examine within-person processes of emotion regulation, including the multiple levels on which emotions occur (physiology, experience, behavior, context, and nonverbal expressions). It thereby provides a basis for understanding competent emotion regulation, the well-being paradox, and emotionally critical periods. Such insights can be utilized to detect person-specific critical periods and for designing immediate person-specific interventions. Although this is still a vision, the benefits of such an approach seem invaluable. The major part of this paper is organized around three general principles that we suggest to further tap the potential of AA in aging research, namely (1) identify within-subject processes and their relations to important life outcomes; (2) capitalize on the full scope of AA technology via multivariate assessments, and (3) combine real-time monitoring with real-time interventions.